PENYUSUNAN LAPORAN KEUANGAN ENTITAS BERORIENTASI NONLABA BERDASARKAN ISAK 335 DENGAN MENGGUNAKAN MICROSOFT EXCEL - Persada, Fikri Dwiputra; Purwohedi , Unggul; Nindito , Marselisa (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze the financial reporting preparation that has been implemented at the Jami Tarbiyatul Falah Mosque and to prepare financial reports based on ISAK 335 using Microsoft Excel. The research design used is descriptive qualitative and case study technique. Data sources using primary and secondary data with data collection techniques through interviews, observations, and documentation. Data validity techniques in this study use source triangulation and technique triangulation. In this study, the researcher analyzes the data by reducing data, presenting data, and drawing conclusions. The results of the study show that the preparation of financial reports that have been carried out by the Mosque, including income and expenditure reports, cash flow statements, general ledgers, and balance sheets, are prepared simply so they do not meet ISAK 335. Then this research produces a mosque financial report prepared based on ISAK 335 using Microsoft Excel.